(untitled) (Tzintzun, Revista de Estudios Históricos, 2021)
The arrival to the island of Cuba of the first coolies was celebrated by the landowners due to the alleged labour predisposed characteristics of these people. But more than the qualities their employers gave them, it was really about strengthening the labour market with hiring modalities that, were close to slavery, were based on coercive work and the availability of workers. The Asian, working freemen, found themselves subjected to a contract of submission and obliged to honor it. Those who had to seek rehiring saw their possibility of leaving fading away. In the present text we examine the rehiring of coolies during the decade of 1860 as well as the role of the State who acted as a protector, but also as a contractor, and the mechanisms implemented by the landowners to subjugate the workers. The rehiring of coolies perpetuated the disguised existence of coercive labour and extended this condition beyond the end of such contracts.